Correlation between estimated glucose disposal rate and diabetic depression: a population-based study - Shao, Xiangzhi; Dai, Huifang; Zhu, Lielie (Frontiers in Psychiatry, 2025)
BackgroundEmerging evidence has identified a correlation between depression and insulin resistance (IR). This study aims to explore the correlation between estimated glucose disposal rate (eGDR)—a noninvasive and practical measure of IR—and depression in patients with diabetes mellitus (DM).MethodsIn this cross-sectional study, the data from 3,080 adults aged 18 years old or older with DM obtained from NHANES 1999–2018 were analyzed. The correlation between eGDR and depression were examined through multivariate logistic regression, subgroup analyses, restricted cubic spline (RCS) analysis, and interaction tests. Additionally, mediation analysis was conducted to assess whether leukocytes and neutrophils could mediate the effects of eGDR on depression.ResultsMultivariate logistic regression and RCS analyses demonstrate that eGDR was negative linearly correlated with diabetic depression (OR= 0.89; 95% CI: 0.84, 0.95). Patients with DM in Q3 and Q4 of eGDR exhibited a reduced risk of 28% and 54%, respectively, in depression, compared to those in Q1. Subgroup analyses, stratified by variables such as gender, BMI, age, education level, and medical comorbidities, consistently showed a negative correlation. Mediation analysis further indicates that neutrophils and leukocytes accounted for 4.0% and 3.6% of the correlation between eGDR and depression, respectively.ConclusionsThe results of this study demonstrated a statistically significant inverse linear correlation between eGDR and the prevalence of depression in patients with DM, with leukocytes and neutrophils acting as mediating factors in this correlation.